2013
DOI: 10.1371/journal.pone.0062853
|View full text |Cite
|
Sign up to set email alerts
|

IL-22-Producing RORγt-Dependent Innate Lymphoid Cells Play a Novel Protective Role in Murine Acute Hepatitis

Abstract: Retinoid-related orphan receptor (ROR) γt is known to be related to the development and function of various immunological compartments in the liver, such as Th17 cells, natural killer T (NKT) cells, and innate lymphoid cells (ILCs). We evaluated the roles of RORγt-expressing cells in mouse acute hepatitis model using RORγt deficient (RORγt−/−) mice and RAG-2 and RORγt double deficient (RAG-2−/− × RORγt−/−) mice. Acute hepatitis was induced in mice by injection with carbon tetrachloride (CCl4), to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 27 publications
(62 reference statements)
0
31
0
Order By: Relevance
“…IL-22 acts on thymic epithelial cells to promote cell survival and proliferation 92 . Further, IL-22-dependent tissue repair in mice has also been reported in the liver following chemical-induced hepatitis 79 and lung following influenza infection or bleomycin-induced damage 87,93,94 , which are two other organs where the tissue resident non-hematopoietic cells highly express the IL-22 receptor 8 .…”
Section: Ilcs Promote the Resolution Of Inflammation And Tissue Repairmentioning
confidence: 94%
“…IL-22 acts on thymic epithelial cells to promote cell survival and proliferation 92 . Further, IL-22-dependent tissue repair in mice has also been reported in the liver following chemical-induced hepatitis 79 and lung following influenza infection or bleomycin-induced damage 87,93,94 , which are two other organs where the tissue resident non-hematopoietic cells highly express the IL-22 receptor 8 .…”
Section: Ilcs Promote the Resolution Of Inflammation And Tissue Repairmentioning
confidence: 94%
“…After damage to the thymus, as seen after whole‐body irradiation, radio‐resistant ILC3 support thymus regeneration by the secretion of IL‐22 . ILC3‐derived IL‐22 is also an important driver in liver tissue repair after chemically induced hepatitis …”
Section: Ilc As Guardians Of Tissue Homeostasis Epithelial Remodelinmentioning
confidence: 99%
“…In the last several years, ILCs have been found to be involved in innate immunity as well as tissue remodeling (32). In the liver, ILCs have been shown to protect against acute hepatitis (33, 34), but can also mediate hepatic fibrosis (35). In addition, we found that IL-17 signaling was important for adaptive T cell responses in viral hepatitis.…”
Section: Introductionmentioning
confidence: 99%